Determining the optimal PD‐1/PD‐L1 inhibitors for the first‐line treatment of non‐small‐cell lung cancer with high‐level PD‐L1 expression in China - Meng‐Meng Teng; Si‐Ying Chen; Bo Yang; Yan Wang; Rui‐Ying Han; Meng‐Na An; Ya‐lin Dong; Hai‐Sheng You (Cancer Medicine, 2021)
Abstract Background and Objective The programmed death 1 and ligand (PD‐1/PD‐L1) inhibitors have significantly altered therapeutic perspectives on non‐small‐cell lung cancer (NSCLC). However, their efficacy and safety are unknown since direct clinical trials have not yet been performed on them. It is also necessary to determine the economics of PD‐1/PD‐L1 inhibitors due to their high cost. The aim was to evaluate the efficacy, safety, and cost‐effectiveness of PD‐1/PD‐L1 inhibitor monotherapy for advanced NSCLC patients in China with high PD‐L1 expression as first‐line treatment. Methods From the PubMed, Cochrane, and Web of Science databases, we retrieved survival, progression, and safety data on PD‐1/PD‐L1 inhibitor monotherapy for advanced NSCLC patients. A network meta‐analysis (NMA) was performed to consider PD‐1/PD‐L1 inhibitors in efficacy and safety. A Markov model with a full‐lifetime horizon was adopted. Clinical and utility data were collected through the trial. The cost per quality‐adjusted life year (QALY) was as incremental cost‐effectiveness ratio (ICER). Sensitivity analyses were performed. Results This study included five phase III clinical trials using four drugs: nivolumab, pembrolizumab, atezolizumab, and durvalumab. The NMA demonstrated that the four drugs had similar efficacy and safety, while pembrolizumab and atezolizumab were better for than for nivolumab (hazard ratio (HR) = 0.66, 95% confidence intervals (CIs): 0.46–0.95 and HR = 0.59, 95%CI: 0.37–0.94) in progression‐free survival (PFS), and the risk of a severe adverse event was higher for atezolizumab than for nivolumab and pembrolizumab. Compared with nivolumab, durvalumab, pembrolizumab, and atezolizumab had QALY of 0.19, 0.38, and 0.53, respectively, which induced ICERs of $ 197,028.8/QALY, $ 111,859.0/QALY, and $ 76,182.3/QALY, respectively. Conclusion The efficacy and safety are similar among types of PD‐1/PD‐L1‐inhibitor monotherapy. The cost‐effectiveness of nivolumab appears optimal, but the other PD‐1/PD‐L1 inhibitors are not as cost‐effective for the first‐line treatment of advanced NSCLC in China.